Inter-cell interference coordination in heterogeneous network: a qualitative and quantitative analysis - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Hassan Abdalla Hashim, Aisha; Abdullah, Khaizuran; Mohd. Ramli, Huda Adibah; Islam, Shayla; Mohamad, Hafizal (IEEE, 2013)
Heterogeneous Networks (HetNet) comprise networks with specially designed architecture. To cover large areas, established base stations (macro sites) are used; for coating buildings, microcells are employed; for covering individual levels or floors in a building, Pico-cells are utilized; and finally for providing wireless coverage to individual apartments, small offices, and home based businesses, femtocells (HeNodeBs) are exploited. The goal behind the implementation of HetNets involves incrementing the capacity, modifying spectrum use, lowering the capital and operating costs, as well as offering steady user-based experience of network architecture. Furthermore, HeNodeBs have been developed for voice, data, video services in home and offices and a certain outdoor scenario with a very limited geographical coverage. However, these random HeNodeB deployments raises co-tier and cross-tier intercell interference which results system performance degradation. The existing approaches have tried to solve Inter-cell Interference (ICI) issues. Yet, these techniques are become unsatisfactory for recent communications as aggressive frequency reuse is desired to maintain high data-rates. In this paper, we investigated and identified recent issues of inter-cell interference coordination problems. The related schemes and techniques are also analyzed in order to highlight the pros and cons of each of the schemes. Besides, the qualitative and the quantitative analysis of these techniques are also presented.